Flipping in the housing market - Charles Ka Yui Leung; Chung-Yi Tse (Osaka University, Institute of Social and Economic Research (ISER), 2017)
We add arbitraging middlemen - investors who attempt to profit from buying low and selling high - to a canonical housing market search model. Flipping tends to take place in sluggish and tight, but not in moderate, markets. To follow is the possibility of multiple equilibria. In one equilibrium, most, if not all, transactions are intermediated, resulting in rapid turnover, a high vacancy rate, and high housing prices. In another equilibrium, few houses are bought and sold by middlemen. Turnover is slow, few houses are vacant, and prices are moderate. Moreover, flippers can enter and exit en masse in response to the smallest interest rate shock. The housing market can then be intrinsically unstable even when all flippers are akin to the arbitraging middlemen in classical finance theory. In speeding up turnover, the flipping that takes place in a sluggish and illiquid market tends to be socially beneficial. The flipping that takes place in a tight and liquid market can be wasteful as the efficiency gain from any faster turnover is unlikely to be large enough to offset the loss from more houses being left vacant in the hands of flippers. Based on our calibrated model, which matches several stylized facts of the U.S. housing market, we show that the housing price response to interest rate change is very non-linear, suggesting cautions to policy attempt to "stabilize" the housing market through monetary policy.
Keywords: D83; R30; G12; 330; Search and matching; housing market; liquidity; flippers and speculators; financing and bargaining advantage